The Infection of Competitive Experience-Ability in Forming the Psychophysiologic Variable Rates of Competitive Anxiety in Age Croup Swimmers - Loupos, Δημήτριος; Moschopoulou, Φωτεινή; Zafiriadis, Στέφανος; Skouridou, Αλεξία; Tsalis, Γεώργιος (Inquiries in Physical Education and Sport, 2008)
The purpose of this project is to explore the changes that can be detected in the competitive anxiety through the improvement of competition experience. These changes can be detected in the cardiovascular function (heart-rate, blood pressure) and the self-report anxiety of the participants. Nineteen (N=19) swimmers, aged 13 years old, participated in this project. During winter championships of northern Greece, the blood pressure, heart-rate and pre-competition anxiety were measured, 30' before the competition. For the evaluation of self-report anxiety it was used the Greek issue of CSAI-2. Next year, in the same championships, athletes repeated exactly the same measures in the same way as the year before. Results indicated decrease of cognitive (t = 1.85, p< .05) and somatic anxiety (t = 2.06, p< .05), systolic (t = 3.48, p< .05) and diastolic (t= 2.12, p< .05) blood pressure and heart-rate (t = 2.97, p< .05), during the second competition. This results show decrease of psychophysiological arousal in the second competition, that is possible to be attributed due to higher level of competition experience.